2020
DOI: 10.1177/1084822320925801
|View full text |Cite
|
Sign up to set email alerts
|

Simulation to Teach Safe Patient Handling and Mobility for Home Caregivers

Abstract: Safe patient handling and mobility (SPHM) programs are needed in the home care environment. As patient-lifting technology and devices become more widely available for use in the home setting, caregivers need opportunities to learn how to properly use these devices. Nonmedical caregivers employed by personal support services agencies (PSSAs) and home caregivers have very limited access to opportunities for SPHM training in rural areas of Tennessee. Safe patient handling and mobility training utilizing simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 10 publications
(7 reference statements)
0
15
0
Order By: Relevance
“…Most results were measured by surveys, but some studies used methods to measure confidence in the relevant area after directly observing or performing the skill according to the characteristics of the simulation. 24,27 Knowledge 23,27,28 and depression 21,29 were the most common outcome measurement concepts; in addition, confidence, 23,25 anxiety, 21,29 and well-being 22,28 were included. Pilot test studies also reported outcomes related to the evaluation of interventions, such as usefulness 21,26 and satisfaction with training.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Most results were measured by surveys, but some studies used methods to measure confidence in the relevant area after directly observing or performing the skill according to the characteristics of the simulation. 24,27 Knowledge 23,27,28 and depression 21,29 were the most common outcome measurement concepts; in addition, confidence, 23,25 anxiety, 21,29 and well-being 22,28 were included. Pilot test studies also reported outcomes related to the evaluation of interventions, such as usefulness 21,26 and satisfaction with training.…”
Section: Discussionmentioning
confidence: 99%
“…Pilot test studies also reported outcomes related to the evaluation of interventions, such as usefulness 21,26 and satisfaction with training. 23,29 Some studies used qualitative data to support the effects of interventions. 21,28 For example, each part of the intervention (simulator and group meeting) was useful to family caregivers, but many family caregivers were skeptical that this entire training experience would prepare them better.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations